Territorial Claims in North Polar Maritime Zone in View of International Security - Xhelilaj, Ermal; Lapa, Kristofor (Transactions on Maritime Science, 2022)
The main feature of the political relations, developed among the coastal states with strong interests over the North Pole region and the Arctic Ocean, have been the frequent interstate disputes over the last fifty years, as well as the efforts of these Arctic states during this period to cooperate in so that the sovereignty and sovereign rights of each coastal state over this region turn into a common benefit for the entire international community. Consequently, sovereignty and sovereign rights are considered fundamental factors for interstate relations in the Arctic Ocean region, for which coastal states have historically been willing to engage in political or military conflicts. The Arctic Ocean, including North Pole maritime region, is governed by customary international law and the law of the sea, which are largely represented by UNCLOS (1982) and the Geneva Conventions on the Law of the Sea (1958). Four Arctic coastal states, Canada, Norway, Denmark, and Russia have ratified these international conventions, while the US accepts its main provisions as norms of customary international law, but is also in the process of ratifying UNCLOS. The purpose of this article is to analyze and discuss the legal, practical, and political situation regarding the delimitation of maritime zones in the North Pole region and the Arctic Ocean, addressing interstate disputes over the major economic, strategic and geopolitical interests of this maritime area in the context of international security.